Three case series involving progresive motor deficit - Bogdan Pana; Alina Anghel; Iuliana Nicola-Antoniu; Ioan Buraga (Romanian Journal of Neurology, 2016)
The muscular dystrophies are a group of inherited, non-inflammatory disorders, consisting of progressive muscle wasting, without peripheral or central nerve involvement. We present a series of three cases involving progressive motor deﬁcit and their different evolutions. The ﬁrst case is about a 57-year-old female patient, without a signiﬁcant family medical history, presenting for progressive motor deﬁcit involving the shoulder and pelvic muscles, started at the age of 20-year-old, when she was diagnosed with a sporadic form of limb-girdle muscular dystrophy. The second case is about a 27-year-old male, diagnosed with muscular dystrophy at the age of 15. The third case is about a 43-year-old male admitted for frequent falls and weakness of the limbs, mainly distal, started 10 years ago. He was diagnosed with myotonic dystrophy. Although there is still no treatment for muscular dystrophies, the pathology is under investigation in clinical trials.